PENERAPAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SD ISLAM AL AZHAR 32 PADANG - Mila Sari; Dewi Citra Rusyadi; Diana Syahfitri; Erman Har; Karmila Suryani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The use of technology-based learning media is one of the strategic efforts to improve the quality of learning in elementary schools in line with the growing demands of 21st century education. This study aims to describe the application of technology-based learning media and analyze its contribution to improving the quality of learning at SD Islam Al Azhar 32. This study uses a qualitative approach with a descriptive research type. The research subjects included elementary school teachers and students, while data collection techniques were carried out through observation, interviews, and documentation. The technology-based learning media used in this study included Canva as a medium for presenting material, learning videos as a means of deepening concepts, and Wordwall as a medium for learning evaluation. The results of the study indicate that the application of technology-based media can increase student activity, motivation, and involvement in the learning process. In addition, the use of technological media encourages teachers to be more creative and innovative in designing and implementing learning. However, the application of technology-based media still faces obstacles in the form of limited digital literacy among teachers and infrastructure support. Overall, this study concludes that the application of technology-based learning media has a positive impact on the quality of learning at SD Islam Al Azhar 32 and needs to be developed continuously with the support of teacher competence and adequate infrastructure